Analisis Penambahan Lini Produksi pada PT XYZ pada Proses Pembuatan Alat Steam Sterilizer Menggunakan Metode Incremental Cost Analysis - Nabila, Talitha Asa; Chumaidiyah, Endang; Sulistiyo, Budi (IAI Nasional Laa Roiba Bogor, 2024)
PT XYZ manufactures medical equipment, including the Steam Sterilizer Autoclave MD 25L. With the increasing demand for healthcare products, particularly the Autoclave MD 25L, production capacity reached its maximum by 2024, causing excessive strain on the workforce. Consequently, alternatives are needed to enhance production capacity without overburdening employees. The decision analysis for expanding the production line was conducted using the incremental cost analysis method, resulting in three alternatives: the existing design, adding one grinding machine and employees, and adding one bending machine and employees. The feasibility analysis confirmed that all three alternatives are viable. Alternative 3 has the highest investment cost, followed by alternative 2, while alternative 1 has the lowest. Initial iterations focused on alternatives 3 and 2, showing a ΔROR of 89.06% with a MARR of 18.36%. Since ΔROR > MARR, alternative 3 was chosen. In the second iteration, comparing alternative 3 with alternative 1 yielded a ΔROR of 77.51%, confirming that alternative 3 remains the best option.